The effectiveness of per-oral carbohydrate and electrolyte solution for enhanced recovery after surgery (ERAS) in pediatric surgery: A randomized clinical trial - Andi Ade Wijaya Ramlan; Christopher Kapuangan; Raihanita Zahra; Rahendra Rahendra; Komang Ayu Ferdiana; Titis Prawitasari; Willy Yant Kartolo; Ivana Firman; Andana Haris; Nathasha Brigitta Selene (Journal of Pediatric Surgery Open)
Introduction: Preoperative fasting in children is necessary to prevent aspiration pneumonia, but prolonged fasting can lead to hypoglycemia, dehydration, electrolyte imbalance, and postoperative nausea and vomiting (PONV). Preoperative carbohydrate loading, part of Enhanced Recovery After Surgery (ERAS), may alleviate discomfort and improve recovery. Methods: This controlled trial randomized 137 children aged 1 to 12 years undergoing elective surgery lasting <6 h into two groups: Carbohydrate-Electrolyte (CE) fluid (n = 67) and clear water (CW) (n = 70). Participants received 50 mL/kg of the assigned fluid following the standard 6–4–1 fasting regimen (solid food, breast milk, clear fluids). Primary outcomes included comparisons of blood glucose and electrolyte levels before and after induction. Secondary outcomes assessed preoperative anxiety, thirst, hunger, PONV, emergence delirium (ED), and pain scores. Results: Blood glucose levels remained within normal limits with no significant differences between groups (p > 0.05), with the CW group exhibiting lower mean glucose levels. Electrolyte levels were similar across groups. Preoperative anxiety, hunger, and postoperative pain showed no significant differences, while preoperative thirst was higher in the CW group (P = 0.040). ED occurred in 5.9 % of patients, with significantly lower scores in the CE group (P = 0.010). Postoperative nausea was more prevalent in the CW group (19.1 %) compared to the CE group (6 %) (P = 0.036). Conclusion: Preoperative CE fluid administration stabilizes blood glucose and electrolyte levels while reducing preoperative thirst, postoperative nausea, and potentially ED compared to CW. These indicate that CE fluids may improve perioperative comfort and outcomes in pediatric patients.